Faktor Faktor Yang Berhubungan Dengan Implementasi Program Pengendalian Tuberkulosis di Puskesmas Wilayah Kabupaten Magelang - Ita Puji Lestari; Laksmono Widagdo; Sakundarno Adi (Universitas Ngudi Waluyo, 2019)
The prevalence of TB in Central Java in 2012 was 106.42 per 100,000 people. The cases and Case Detection Rate below the standard of 70% are found in the level of cities, regencies or health centers. The lowest CDR is in Magelang regency which is 21.82%. In 2013, it is estimated that there were new cases of lung TB in Magelang regency and there were 1,285 people suffering from positive BTA in 2013 reached 17.89%. This research aims to know the factors related to the implementation in the program of controlling TB in Public Health Centers in Magelang regency. This research was observational analytic using Cross Sectional Approach. The population was all executive employees consisting of one nurse as the program coordinator, one laboratory employee, and a doctor as many as 87 people. Data analysis was done by using bivariat. The research results using statistical test showed that there was a correlation between communication factors and the implementation (p value=0,001), there was a correlation between dispositional factors and the implementation (p value=0,001), there was a correlation between characteristic of Public Health Centers and the implementation of program to control TB (p value=0,001), there was a correlation between the factors of understanding factors and the targets and the implementation (p value =0,013), there was no correlation between resources factor and the implementation of TB program (p value=0,240), and there was no correlation between environmental factors and the implementation of TB program (p value =0,057). Public Health Centers have to compile the instruments to measure the effectiveness of the coordination in the program, and to make the activities of education and cadre training of TB disease periodically. Public Health Center should make cooperative networks with stakeholders and society, should compile the development of reward system for the employees and TB cadres who have contribution and active roles, and should compile a specific task force for the program of controlling TB which are legalized with the decree letter from the Public Health Center.